(untitled) (Architecture Image Studies, 2025)
The text is created from 3D scans of Virginia Woolf’s writing hut and garden located in the house where she lived from 1918 until her death in 1941: Monk’s House in Rodmell, East Sussex. The scans capture the garden in ways that appear both substantial and yet ethereal, tracing contours that explore the physical textures of the site while using movement to allude to the cadences and syntax of the text. The film has been developed using Woolf’s 1931 experimental novel ‘The Waves’ as a narrative armature. The ‘camera’ moves through the garden, mapping out different perspectives with a steady pace and rhythm, tracing dreamlike vectors as if motivated by the desire-lines of Woolf’s restless characters. After a sequence that implies confusion and disorientation, the final tracking shot returns us to the hut, as a voice previously buried and scrambled in the soundtrack reads a particularly poignant section of the novel. Author Biographies Nic Clear, Professor of Architecture & Dean of School of Arts and Humanities, University of Huddersfield Professor Nic Clear is a qualified architect, writer and curator. He is Professor of Architecture and Dean of the School of Arts and Humanities at the University of Huddersfield. He was a Professor of Architecture and Head of the Department of Architecture and Landscape at the University of Greenwich, having previously taught at the Bartlett School of Architecture for over 20 years. In 2015, he was the Inaugural Professor for Research in Visionary Cities at the Institute of Fine Arts in Vienna, and has taught in the UK, Europe, the US and Canada. Hyun Jun Park, Course Director Postgraduate Architecture, Leeds Beckett University Hyun Jun Park is a practitioner, writer, curator, fellow of the Royal Society of Arts and Course Director for Postgraduate Architecture at the Leeds School of Architecture, Leeds Beckett University. Prior to this, he was Course Leader for the Master of Architecture at the University of Huddersfield and taught postgraduate M.Arch design studio at the University of Greenwich. Before he came to the UK, he was an associate architect at SAMOO Architects & Engineers (SAMSUNG Corp), Seoul, Korea. He was awarded M.Arch by the Bartlett School of Architecture and finished his BA and first master’s degree at Hongik University, Seoul, Korea. Clear + Park Clear+Park use 3D laser scanning to create multidisciplinary works that operate across architecture, installation, and media arts. Clear+Park use 3D scanning to capture spaces and create spatial representations and narratives that engage with, and respond to specific site histories and spatial practices. Through their research Clear+Park explore ways in which architects and artists can reproduce, develop, manipulate, and represent spaces using advanced digital technology in ways that engage with non-specialist audiences.